Perpaduan Pembelajaran Berbasis Masalah dan Cooperstive Script Mampu Memberdayakan Pemahaman Konsep Biologi Siswa - Didimus Tanah Boleng (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
A quasi-experimental study has been conducted at Samarinda senior high school. The study was carried out in the odd semester of the 2016/2017 learning year, the X1th class of the Department of Natural Sciences. The purpose of this research is to know the influence of the application of combined of problem based learning and Cooperative script to the understanding of student biology concept.  The study design was nonequivalent pretest - posttest control group design.  The sample of research is the students of class XI taken by purposive sampling.  Research instrument in the form of test questions. Data analysis technique is t test for unpaired sample. The result of data analysis shows that the tcount is -15,05; and ttable value (df = 54), (α = 0,05; 1 2α = 0,025) is 2,00; it is concluded that there is influence of application of combined of problem based learning and Cooperative script to understanding student biology concept.  Similar research needs to be done by taking larger sample numbers to get more information.